2011
DOI: 10.1007/978-3-642-27257-8_12
|View full text |Cite
|
Sign up to set email alerts
|

A Hardware Processor Supporting Elliptic Curve Cryptography for Less than 9 kGEs

Abstract: Abstract. Elliptic Curve Cryptography (ECC) based processors have gained large attention in the context of embedded-system design due to their ability of efficient implementation. In this paper, we present a lowresource processor that supports ECC operations for less than 9 kGEs. We base our design on an optimized 16-bit microcontroller that provides high flexibility and scalability for various applications. The design allows the use of an optimized RAM-macro block and reduces the complexity by sharing various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…B) for area and cycles of ECC coprocessors that follow the design decisions presented in this paper and perform point multiplications on curves B-163 or K-163. Our estimates show that our coprocessors for both B-163 and K-163 require more cycles in comparison to [43] which also uses a 16-bit ALU. The reason behind this is that [43] uses a dual-port RAM, whereas our implementation uses a single-port RAM (as it works as a coprocessor of MSP430).…”
Section: Results and Comparisonsmentioning
confidence: 94%
“…B) for area and cycles of ECC coprocessors that follow the design decisions presented in this paper and perform point multiplications on curves B-163 or K-163. Our estimates show that our coprocessors for both B-163 and K-163 require more cycles in comparison to [43] which also uses a 16-bit ALU. The reason behind this is that [43] uses a dual-port RAM, whereas our implementation uses a single-port RAM (as it works as a coprocessor of MSP430).…”
Section: Results and Comparisonsmentioning
confidence: 94%
“…As a controller, we decided to use our own 16-bit microcontroller called Neptun [33,34,35] that is especially optimized for elliptic-curve cryptography. The processor comes with twelve special-purpose registers and uses a Harvard architecture with separated program and data memory.…”
Section: Comparison Resultsmentioning
confidence: 99%
“…For instance, in [34,33] and [35], Ould-Slimane et al give an automata based inlining procedure which relies on a new operator that embeds a property automata into a target program. For instance, in [34,33] and [35], Ould-Slimane et al give an automata based inlining procedure which relies on a new operator that embeds a property automata into a target program.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Lee et al [22,23] and Wenger and Hutter [33] showed that public-key cryptography can be implemented. More specifically, these papers proposed efficient dedicated coprocessors that can do elliptic curve arithmetic on curves suitable for Elliptic Curve Cryptography (ECC).…”
Section: Introductionmentioning
confidence: 98%